HUBUNGAN KELELAHAN DENGAN KEMAMPUAN KERJA KARYAWAN BAGIAN HOUSEKEEPING HOTEL BINTANG TIGA DI DENPASAR - Suastini, Ni Kadek; Adiputra, I Nyoman (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2015)
Tourism has become one of the engines of socio-economic progress for many countries. The number of  users  star hotel facilities  makes  the hotel more  extra  employees  in negotiating the arrangement of the hotel especially the housekeeping employees who workwith emphasis on physical strength as the center of activities that affect the fatigue and employability.  This study analyzed  the correlation between  fatigue  and work ability. Research  conducted  observational  (non-experimental) with a  cross-sectional  analytic 59approach. The number of respondents consisted of 31 respondents consisting of employees of the housekeeping three stars hotel in Denpasar, to fill in the questionnaire Work AbilityIndex and the 30 item questionnaire rating scale of the Japan Association of IndustrialHealth and Industrial Fatigue Research Committee of Japan. From the research, there is40.81 ± 9.35 mean of fatigue. While, the average of work ability is 41.25 ± 4.15. There is asignificant relationship between the fatigue and the work ability with the value of (p =0.011) and values of (r = -0,450). The p-value indicates there is a significant relationshipbetween fatigue and work ability, the value of r indicates the direction opposite relationshipbetween fatigue and work ability. It can be concluded that there is a relationship betweenfatigue with the work ability of employees at the hotel housekeeping. For the hotel need to know the fatigue scores of each individual to improve the employees work especially those working in the field of physical and mental.
Keywords: fatigue, work ability, housekeeping